Approach to Robust and Elegant Bridge Design. Issue 4 (2nd October 2021) - Tanner, Peter; Hingorani, Ramon
Abstract: In bridge planning, the successful translation of the many conditioning factors into a solution that meets all safety requirements while also addressing considerations such as economy and elegance is essentially a matter of conceptual design. Despite the utmost importance of that stage, which in addition to an intuitive understanding of load-bearing mechanisms calls for imagination and a sense of form and beauty, creative conceptual thinking is systematically underestimated both in engineering training and everyday practice. The resulting impoverishment of the profession stems not only from growing, need-driven and hardly reversible specialisation, but also from inexorably extensive and opaque standardisation and control. The rules for ensuring robustness reflect the increasing complexity and opacity characterising structural design codes. While the practical importance of designing and building robust structures is universally acknowledged, the codes presently in place are often vague or confusing. Cross-referencing, in turn, may lead to loops around rules that, confounding engineers, are counterproductive. At the same time, however, that lack of clarity may afford opportunities for innovative solutions by building items that ensure robustness into the conceptual design of a structure. This paper proposes an operational design process that deals appropriately with all factors of structural performance, including robustness, without compromising bridge economy or elegance. That process, which combines a number of robustness strategies, including risk-based considerations, is illustrated with a case study of a proposal submitted to a design competition for a viaduct.